2021
DOI: 10.5853/jos.2021.01249
|View full text |Cite
|
Sign up to set email alerts
|

Role of Blood Lipid Levels and Lipid-Lowering Therapy in Stroke Patients with Different Levels of Cerebral Artery Diseases: Reconsidering Recent Stroke Guidelines

Abstract: Hyperlipidemia is an important risk factor for ischemic stroke; the Stroke Prevention by Aggressive Reduction in Cholesterol Level and Treat Stroke to Target studies have shown that statins are beneficial for patients with stroke and that a low target for low-density lipoprotein cholesterol (LDL-C) concentration may maximize this benefit. Based on these results, recent guidelines have emphasized the application of “high-intensity statins” and “low LDL-C target” strategies in patients with stroke. However, it s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 72 publications
0
21
0
Order By: Relevance
“…The heterogeneity of causes of index stroke, as well as recurrent stroke, may be 1 major factor associated with such a phenomenon. The benefits associated with LDL-C–lowering statin-based therapies vary among patients with stroke owing to the different causes, and there are concerns that such a strategy may not be universally beneficial to all patients with ischemic stroke . We found that more intensive LDL-C–lowering statin-based therapies were associated with a reduced risk of recurrent stroke only in trials with all patients having evidence of atherosclerosis.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The heterogeneity of causes of index stroke, as well as recurrent stroke, may be 1 major factor associated with such a phenomenon. The benefits associated with LDL-C–lowering statin-based therapies vary among patients with stroke owing to the different causes, and there are concerns that such a strategy may not be universally beneficial to all patients with ischemic stroke . We found that more intensive LDL-C–lowering statin-based therapies were associated with a reduced risk of recurrent stroke only in trials with all patients having evidence of atherosclerosis.…”
Section: Discussionmentioning
confidence: 80%
“…One included trial performed in Japan comparing pravastatin, 10 mg daily, with placebo did not show a reduction in the risk of recurrent stroke . In the TST Trial, although the lower-target strategy was superior to the higher-target strategy in the French population, the benefit of the lower target was not shown for either major cardiovascular events or in recurrent stroke when South Korean patients were analyzed separately . Because the risk of recurrent stroke was not reduced by LDL-C–lowering statin-based therapies in randomized clinical trials of Asian populations, it is therefore not known whether the benefit associated with more intensive LDL-C–lowering statin-based therapies for secondary stroke prevention should be generalized to Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic disturbance of blood lipids as well-established vascular factors seemed to have a potential role in small vessel disease, especially high-density lipoprotein [ 39 ]. Lipid-modifying therapies have shown benefits in the prevention of ischaemic small vessel disease and leukoaraiosis [ 50 ]. The apolipoprotein E(APOE) as the main carrier regulated the transport and metabolism of cholesterol in the periphery and CNS, and APOE polymorphism was strongly related to neurodegeneration and dementia [ 51 ].…”
Section: The Underlying Role Of the Glymphatic And Meningeal Lymphati...mentioning
confidence: 99%
“…Guidelines for secondary prevention of stroke underscore a tailored therapeutic approach based on stroke subtypes, 25,26 recommending strict blood pressure management for SVO strokes, 27 intensive antiplatelet and lipid-lowering therapy for LAA strokes, [28][29][30][31] and anticoagulant therapy for CE strokes. 32 However, a quarter of strokes are classified as embolic stroke with undetermined source (ESUS).…”
Section: Discussionmentioning
confidence: 99%